Campus sustentável e educação : desafios ambientais para a universidade - Wachholz, Chalissa Beatriz (2017)
This thesis present the process of environmentalization of two Brazilian universities and a Spanish one: the Pontifical Catholic University of Rio Grande do Sul (PUCRS), the University of Lavras (UFLA), and the University of Alcalá (UAH), respectively. The main focus of this research is to understand how sustainability is being addressed in the activities of these institutions and what is the greatest challenge in the continuity of these actions. Considering that the environmentalization is a process that addresses the socio-environmental dimension in all axes and actions and taking into account the historical retrospective of this process in higher education, the role of indicators and the networks woven in this scenario, this research understands that the environmentalization occurs in three dimensions: in management, in the curriculum and in the campus. Based on this definition, the study aims to identify the main actions and challenges in each of these dimensions. The choice of these universities was based on my experience as a student at PUCRS and the rank of the UFLA and the UAH at the GreenMetric World University Ranking, which measures the sustainability of higher education institutions worldwide and shows that these two universities are in the first position in their respective countries. The research has identified the environmental actions of many Brazilian universities, showing the concern of these institutions in assuming their socio-environmental responsibility, the potential of transformation when there is a sustainable management and the fragility in environmental education, which needs to claim more space and strength in these institutions.